Alat Pengolah Limbah Rumah Tangga Menjadi Kompos Berbasis Mikrokontroler - Khakim, Lukmanul; Budihartono, Eko (Komputika : Jurnal Sistem Komputer, 2023)
Households are the largest contributor to waste, various types of waste are generated, ranging from organic, non-organic waste and so on. If each household produces 2 kg of waste every day, and the waste is immediately disposed of in a temporary landfill (TPS), then a very large amount of waste is buried in the TPS. Therefore, a tool is needed that functions to process waste that can be recycled into compost, namely waste or food waste classified as organic waste. The tool in question consists of a nema 17 stepper motor as a cutter and stirrer for garbage to mix with the soil, a YL-69 sensor as a soil moisture detector, a DS18B20 sensor as a soil temperature detector and two mini pumps as a water supply and EM4. From the results of this study, YL-69 detects soil moisture of 17% to 86%, meaning that soil moisture increases, so the stepper will be active to stir the soil and organic waste. Furthermore, DS18B20 detects soil temperatures of 25°C to 34°C, meaning that when the temperature is between 30°C to 34°C, the composting process takes place, the water supply and EM4 stop automatically. Keywords – Organic Waste; Compost; Microcontroller, DS18B20, YL-69.